KAJIAN YURIDIS KEDUDUKAN KOMISARIS DALAM MELAKUKAN KEPENGURUSAN PERSEROAN TERBATAS - Saor Husada, Arthya; Dahana, Cokorda Dalem (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 09, September 2013, 2013)
This study aims to determine the legal consequences caused if the Commissionerdid an arrangement in a limited liability company under Act No. 40 of 2007, while themethods used in this study is normative juridical. Commissioner is one of the importantorgans of the Limited Liability Company, whose main function is to oversee policydirectors in running the company and providing advice to directors. The results showed bythe Articles of Association and the resolution of the GMS, the commissioner may takeaction in the management of the company in certain circumstances and for a specific timeperiod that is accompanied with the same burden of responsibility appropriate role of theboard of directors as a limited liability company.
Keywords: Commissioner, Limited Liability Company, Oversee